Euroticins C–E, three pairs of polycyclic salicylaldehyde derivative enantiomers from a marine-derived fungus Eurotium sp. SCSIO F452. Issue 7 (3rd February 2021) - Zhong, Weimao; Chen, Yuchan; Wei, Xiaoyi; Wang, Junfeng; Zeng, Qi; Tian, Xinpeng; Zhang, Weimin; Wang, Fazuo; Zhang, Si
Abstract : Euroticins C–E (1–3 ) are three pairs of salicylaldehyde derivative enantiomers representing two types of unprecedented highly constructed 6/6/6/6 tetracyclic structures from a marine-derived fungus Eurotium sp. SCSIO F452. Abstract : Euroticins C–E (1–3 ), three pairs of salicylaldehyde derivative enantiomers, were isolated from a marine-derived fungus Eurotium sp. SCSIO F452. They represent two types of salicylaldehyde derivatives bearing unprecedented highly constructed 6/6/6/6 tetracyclic structures. Their structures were established by comprehensive spectroscopic analyses, X-ray diffraction, and electronic circular dichroism calculations. Compounds (+)-1 and (−)-1 showed significant antioxidative activity and moderate cytotoxic activity.